A closer observation of the Pcpt-Cs. system in Freud's thinking and its relation to time perception from a neuroscientific perspective - Pajoohandeh, Ali; Hadi, Maryam; Jafari, Raheleh (Neuro-psychoanalysis (Madison, Conn.), 2024)
In this article, we explore the Pcpt-Cs. (perceptual-consciousness) system in Freud's work and its relation to the subject of time perception, as well as its study from a neuroscience perspective. According to Freud, the Pcpt-Cs. system is a porous system located at the front of the psychic apparatus, on the border of the external and internal worlds. We first offer an overview of the Pcpt-Cs. system in Freud's papers throughout different years of his career. In this regard, we note that Freud considers our perception of time to be the result of a continuous and discontinuous connection between the unconscious and the external world through the Pcpt-Cs. system. In the second part, we review new studies concerning time perception in neuroscience. We suggest that we cannot locate a particular system characterized by the features that Freud attributed to the Pcpt-Cs. system in the brain. Nevertheless, if we are to point out the most similar part of the brain to the Pcpt-Cs. system based on what we have investigated throughout the present article, the systems involved in working memory would be our best suggestion.